New Exact Monoploe Sultions of SU(2) Yang-Mills Gauge Field Equations by Null-Tetrad Formalism - B. V. Baby (Research and Applications Towards Mathematics and Computer Science Vol. 9, 2024)
New closed form solutions of SU(2) Yang-Mills (YM) gauge field equations found by the Carmeli-Charash-Kaye-Kh. Huleihil null-tetrad formalism. Unlike earlier reported solutions with special functions of elliptic integrals, this new solutions are with complex valued circular functions and with two arbitrary integration constants. Electric parts obtained as zero and having only nonzero magnetic parts and so concluded as new magnetic monopole solutions of SU(2) YM gauge filed equations.